Identifying optimal frameworks to implement or evaluate digital health interventions: a scoping review protocol. Issue 8 (13th August 2020) - Soobiah, Charlene; Cooper, Madeline; Kishimoto, Vanessa; Bhatia, R Sacha; Scott, Ted; Maloney, Shelagh; Larsen, Darren; Wijeysundera, Harindra C; Zelmer, Jennifer; Gray, Carolyn Steele; Desveaux, Laura
Abstract : Introduction: Digital health interventions (DHIs) are defined as health services delivered electronically through formal or informal care. DHIs can range from electronic medical records used by providers to mobile health apps used by consumers. DHIs involve complex interactions between user, technology and the healthcare team, posing challenges for implementation and evaluation. Theoretical or interpretive frameworks are crucial in providing researchers guidance and clarity on implementation or evaluation approaches; however, there is a lack of standardisation on which frameworks to use in which contexts. Our goal is to conduct a scoping review to identify frameworks to guide the implementation or evaluation of DHIs. Methods and analysis: A scoping review will be conducted using methods outlined by the Joanna Briggs Institute reviewers' manual and will conform to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Studies will be included if they report on frameworks (ie, theoretical, interpretive, developmental) that are used to guide either implementation or evaluation of DHIs. Electronic databases, including MEDLINE, EMBASE, CINAHL and PsychINFO will be searched in addition to grey literature and reference lists of included studies. Citations and full text articles will be screened independently in Covidence after a reliability check among reviewers. We will use qualitative description to summarise findings and focus on how research objectives and type of DHIs are aligned with the frameworks used. Ethics and dissemination: We engaged an advisory panel of digital health knowledge users to provide input at strategic stages of the scoping review to enhance the relevance of findings and inform dissemination activities. Specifically, they will provide feedback on the eligibility criteria, data abstraction elements, interpretation of findings and assist in developing key messages for dissemination. This study does not require ethical review. Findings from review will support decision making when selecting appropriate frameworks to guide the implementation or evaluation of DHIs.